The Lexical Expression and Its Impact on Stylistic Construction in Iraqi Women's Poetry - Abdulsalam Abdulbari, Assist. Lect. Ekhlas; Abdulhussein Gyadh, Assist .Prof. Dr. Abbas (Basra studies journal, 2024)
A lexical vocabulary is one of the most important components of Creative text. The creator carefully selects his or her own shades of stylistic features and signifiers, showing different semantics Wil's distinctive experiment into his or her own verbal wealth, which distinguishes him or her from others. It also helps to uncover worlds. One word carries a set of semantic openings, and thus works to achieve a plurality of semantics: because the first meanings translate to other meanings: the continental search is always on the horizons. All the hair of Iraqi women is an integral stylistic construction that has its own aesthetic features and features that have made it a security: Because of its accuracy in conveying ticks and semantics, we find that the lexical vocabulary has a remarkable effect of poetry and what distinguished the poetry of Iraqi women by its stylistic construction, and her gentle, twisty touch away from one moment and dismissive at a time, it is calm, loud and her vocabulary came with a broad horizon expressing her and her surroundings and went to clarity and simplicity once more .